The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/adom.202002239
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastable Perovskite Nanocrystals in All‐Inorganic Transparent Matrix for High‐Speed Underwater Wireless Optical Communication

Abstract: The key features of lead halide perovskites, including short emission lifetime and excellent luminous efficiency in the green emission region, perfectly match the strict requirements of underwater wireless optical communication (UWOC). However, the poor stability of perovskite nanocrystals (NCs) restricts its application under water and no relevant application research has been reported. Here, extremely stable CsPbBr3 NCs in all‐inorganic amorphous glass synthesized by all‐solid reaction without any organic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…with high-resolution imaging for electrochemical eye. [297,298] In addition, the utilization of micro-nano structure in colorful and semitransparent optoelectronics provides possibility to meet the application of intelligent building. ii.…”
Section: Discussionmentioning
confidence: 99%
“…with high-resolution imaging for electrochemical eye. [297,298] In addition, the utilization of micro-nano structure in colorful and semitransparent optoelectronics provides possibility to meet the application of intelligent building. ii.…”
Section: Discussionmentioning
confidence: 99%
“…To further demonstrate the outstanding thermal stability of the SCP@MSNs‐PDMS film, the comparisons of the PL retention and cycle number after heating–cooling cycle of SCP@MSNs‐PDMS film with some latest reported results were shown in Figure 3j. [ 26,33–40 ] It can be observed that even being tested at the highest testing temperature and longest heating–cooling cycles, SCP@MSNs‐PDMS film represented by the asterisk presented the best room temperature PL retention compared with the results reported in the literature, which further proved the ultra‐excellent thermal stability of SCP@MSNs‐PDMS film.…”
Section: Resultsmentioning
confidence: 57%
“…To further demonstrate the outstanding thermal stability of the SCP@MSNs-PDMS film, the comparisons of the PL retention and cycle number after heating-cooling cycle of SCP@MSNs-PDMS film with some latest reported results were shown in Figure 3j. [26,[33][34][35][36][37][38][39][40] It can be observed that even being tested at the highest testing temperature and longest heating-cooling cycles, SCP@MSNs-PDMS film represented by the asterisk presented Small 2022, 18, 2107452 The emission wavelengths of g) CsPbBr 3 QDs, h) SCP-PDMS film, and i) SCP@MSNs-PDMS film after heating-cooling cycle tests at different temperatures (60, 100, 150, 200 °C). j) The comparisons of the PL retention and cycle number after heating-cooling cycle of our results with some latest reported results.…”
Section: Resultsmentioning
confidence: 99%
“…After the pioneering work by Ai et al, CsPbX 3 PNCs have been successfully precipitated in borosilicate glass, 31,32 borogermanate glass, 33,34 borophosphate glass, 30,35 tellurite glasses, 36,37 oxyfluoride glasses, 38 and chalcogenide glasses. 39 Potential applications of these CsPbX 3 PNCs embedded glasses such as lightemitting diodes, 33,36,37 anticounterfeitings, 40 data storage media, 41 scintillators, 42 color filters, 43 and undersea water communications 44 have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%